2018
DOI: 10.1128/iai.00458-17
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Host Polyamines in Alternatively Activated Macrophages Promotes Chronic Infection by Brucella abortus

Abstract: Treatment of intracellular bacterial pathogens with antibiotic therapy often requires a long course of multiple drugs. A barrier to developing strategies that enhance antibiotic efficacy against these pathogens is our poor understanding of the intracellular nutritional environment that maintains bacterial persistence. The intracellular pathogen Brucella abortus survives and replicates preferentially in alternatively activated macrophages (AAMs); however, knowledge of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…The altered metabolic state of M2 macrophages might also support the persistence of intracellular pathogens, which in the case of Salmonella appears dependent on the host transcription factor PPARd (Eisele et al, 2013;Xavier et al, 2013). Indeed, several other pathogens, including Mycobacterium tuberculosis (Huang et al, 2018;Sahu et al, 2017), Coxiella (Benoit et al, 2008), Francisella (Shirey et al, 2008), and Brucella (Kerrinnes et al, 2018), drive an anti-inflammatory M2-like host response. Whereas GRA18 from Toxoplasma gondii interacts with GSK3 and promotes transcription of anti-inflammatory genes, the mechanism is likely to be different because GRA18 functions in a b-catenin-dependent fashion (He et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The altered metabolic state of M2 macrophages might also support the persistence of intracellular pathogens, which in the case of Salmonella appears dependent on the host transcription factor PPARd (Eisele et al, 2013;Xavier et al, 2013). Indeed, several other pathogens, including Mycobacterium tuberculosis (Huang et al, 2018;Sahu et al, 2017), Coxiella (Benoit et al, 2008), Francisella (Shirey et al, 2008), and Brucella (Kerrinnes et al, 2018), drive an anti-inflammatory M2-like host response. Whereas GRA18 from Toxoplasma gondii interacts with GSK3 and promotes transcription of anti-inflammatory genes, the mechanism is likely to be different because GRA18 functions in a b-catenin-dependent fashion (He et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…During intracellular bacterial infections, infected macrophages typically exhibit a classically activated (M1-like) phenotype and restrict the pathogen through mechanisms such as pyroptosis and production of pro-inflammatory cytokines, including tumor necrosis factor (TNF) (Storek and Monack, 2015). Emerging evidence suggests an alternatively activated (M2like) phenotype is associated with intracellular bacterial growth and persistence (Eisele et al, 2013;Huang et al, 2018;Kerrinnes et al, 2018;Sahu et al, 2017;Stapels et al, 2018). Computational modeling studies have shown that the ratio of M1 versus M2 activities within Mycobacterium tuberculosis (Mtb) granulomas can predict controlled infection or disseminated disease (Marino et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The different L-arginine catabolizing pathways have been shown to be of central importance for host resistance to infection with intracellular microbes, mainly by generating the formation of NO to enforce anti-microbial host responses, but also via the synthesis of polyamines, resulting in a pathogen-friendly nutritional environment [ 9 , 44 , 45 , 46 ]. A central enzyme controlling L-arginine levels in infected macrophages is ARG1, which cleaves L-arginine into ornithine and urea and thereby limits the availability of L-arginine for NO formation.…”
Section: Discussionmentioning
confidence: 99%